The Outcome of Design Innovation and the Antecedents of Design Activities: Insights from Canadian Manufacturing Industries - Wang, Shu (My University, 2023)
The importance of product design has been getting attention in the past decade from scholars and practitioners. Design plays a critical role in firms’ product development and business strategies. In recent years, scholars began to see design innovation as another vital innovation element of a new product. A new product should encompass at least two innovation elements: technology innovation and design innovation. While technology points to the function of a product, design points to the form of a product. Despite the advocacy of scholarly examination of design innovation, there are few studies of design innovation. In this dissertation, two empirical studies have been conducted to examine the outcome of design innovation and the antecedents of design activities, respectively. Study 1 examines the effect of design innovation (as well as technology and service innovation) on new product performance. Additionally, the study examines the roles of marketing innovation and process innovation in mediating the relationships between these innovation activities and new product performance. Study 2 examines how firms’ absorptive capacity, competitive responsiveness, and product development resources drive design and R&D activities. Design and R&D activities typically lead to the introduction of design and technology innovation. Regarding the findings from this dissertation, the first study shows that design, technology, and service innovation (which, argued by this study, are the three main innovation elements of a new product) all contribute to new product performance. Additionally, marketing innovation and process innovation are found to mediate the relationship between these innovation elements and performance. The second study shows that a firm’s competitor responsiveness, absorptive capacity (captured by “institutional sources” and “market sources of information”), and product development resources (captured by “cross-functional design team”, “design or information control technologies”, and “concurrent engineering”) are positively related to firms’ design and R&D activities.
Keywords: design innovation; design activities; technology innovation; R&D activities; service innovation